Learning methodology in the classroom to encourage participation (UCL Press, 2014)
Service learning is a methodology that promotes the participation of citizens in their community. This article presents a brief conceptualization of citizen participation, characteristics of servicelearning methodology, and validation of a programme that promotes service-learning projects. This validation highlights the suitability of this methodology for the development of citizen participation.